Vinovata li sportivnaya gimnastika? - Soboleva, T. S.; Sobolev, D. V. (Teorija i Praktika fiziceskoj Kul'tury, 2001)
The actual inquiry of sports practice has given a sharp push to rejuvenation of female sports gymnastics. It is necessary to solve the problem - whether the gymnastics retardation aggravates in girls. The average length of the body in the mothers of the gimnasts-masters of sports was on 10 sm less, than in whole population (accordingly 154 and 164 ??). These results have shown, that there is an expressed artificial selection of the certain natural constitutions adequate requirements of sports gymnastics at the stages of sports selection.